The Jan Vishwas (Amendmentof provisions) act, 2023: Conception and development - Jain, Anurag (Yojana)
(3z(BThe main objective of the act is to decriminalize minor offences that do not involve any harm to the public interest or national security and replace them with civil penalties or administrative actions, minor technical, and procedural defaults not longer attract severs criminal consequences, reducing the burden on the justice system and putting adjudication of serious offences on the priority. Implementation of the Jan Vishwas act essentially means that majority cases originating from 183 portions across 42 acts would not longer be adjudged by the courts(3y(B- Reproduced s
Keywords: Jan Vishwas Amendment of Provisions Bill 2023, Jan Vishwas Act 2023